Physiotherapists’ knowledge on the provision of physiotherapy to people with mental illness. A study from Paraguay - Almirón, Marcos; Barrios, Iván; O’Higgins, Marcelo; González, Israel; Castaldelli-Maia, João Mauricio; Ventriglio, Antonio; Torales, Julio (Medicina Clínica y Social, 2020)
Introduction: Physiotherapy improves the quality of life in people with mental disorders through the optimization of their physical and mental health. This study aimed to determine the knowledge of physiotherapists about the provision of Physiotherapy services to people with mental disorders, about the role of Physiotherapy in the treatment of physical illnesses of mentally ill persons and in the treatment of the mental disorder itself. Methodology: A descriptive, observational, cross-sectional, and prospective study was conducted. 187 physiotherapists practicing in Paraguay, of both sexes, were surveyed. The data collection instrument was a Spanish version of the survey used by Andrew et al., which was adapted. Results: 46.52% of physiotherapists stated that Physiotherapy is useful to manage the physical symptoms of people with mental disorders. 55.61% reported that they needed more information and/or training on managing physical conditions affecting these people. 75.94% declared that they were aware that Physiotherapy can be used as treatment for some mental disorders, mainly as an adjuvant treatment to both pharmacotherapy and psychotherapy (54.55%). Participants scored anxiety disorders (23.88%), major depression disorder (21.99%) and Alzheimer’s disease (21.48%) as those conditions that could most benefit from a physiotherapeutic intervention. Also, 21.93% of the respondents reported the need of more information on how to interact and communicate with people with mental disorders. Conclusion: There are gaps in the knowledge of physiotherapists in Paraguay about the provision of Physiotherapy to people with mental disorders. An adequate training and education of physiotherapists on mental illness is encouraged.